2004
DOI: 10.1002/mame.200300320
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Thermoset Matrix Reinforced with Sugar Cane Bagasse Fibers: Attempt to Develop a New Fiber Surface Chemical Modification Involving Formation of Quinones Followed by Reaction with Furfuryl Alcohol

Abstract: Summary: A new chemical modification of sugar cane bagasse fibers for phenolic thermoset composites is presented. It consists in creating quinones in the lignin portions of fiber and react them with furfuryl alcohol to create a coating around the fiber more compatible with the phenolic resins used to prepare polymeric matrix. Sodium periodate was used in suitable conditions to oxidize mainly phenolic syringyl and guaiacyl units of the lignin polymer to create quinones, which were characterized by UV‐visible di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 25 publications
3
56
1
1
Order By: Relevance
“…[7] The use of lignocellulosic materials as replacements for synthetic fibers in the production of composites has gained significant importance in technical applications, such as in the automotive, as well as in the packaging industries. [8][9][10] Unfortunately, several disadvantages of natural fibers such as mechanical and thermal degradation during processing can make them undesirable for certain applications. Thermal degradation of the fibers occurs above 200 8C, resulting in gaseous products, which can cause high porosity and lower mechanical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] The use of lignocellulosic materials as replacements for synthetic fibers in the production of composites has gained significant importance in technical applications, such as in the automotive, as well as in the packaging industries. [8][9][10] Unfortunately, several disadvantages of natural fibers such as mechanical and thermal degradation during processing can make them undesirable for certain applications. Thermal degradation of the fibers occurs above 200 8C, resulting in gaseous products, which can cause high porosity and lower mechanical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of papers, [9][10][11][12] we have applied a new way of chemically modifying the surface of lignocellulosic fibers. This method involves a selective modification of the lignin polymer partly preserving the cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, either partial degradation of PP occurs, or the extent of the reaction between maleic groups of the compatibilizer and hydroxyl groups of cellulose is increased. In this latter case, a better interfacial adhesion could be obtained as a result of the recycling process of the matrices, and this phenomenon could explain the improvement of the thermal stability and the interesting mechanical response of recycled matrices-based composites [23][24][25] . dispersion but also of the filler/matrix adhesion level after applying an external load.…”
Section: Tga Resultsmentioning
confidence: 95%
“…29,30 Our present research interest concerns ways to transform sugarcane bagasse fibers into useful materials, such as board and composites. 31,32 For board materials in outdoor uses, their photostability might be questionable and the photochemical behavior of these fibers to UVVisible irradiation needs basic knowledge. Very recently, 33 we have shown that acidolysis lignins of peroxide bleached and unbleached bagasse fibers present a high content in p-hydroxyphenylpropane units compared to hardwood and softwood.…”
mentioning
confidence: 99%